THE FORMATION OF KEY COMPETENCES OF THE MODERN MANAGER AS A TOOL FOR EFFECTIVE MANAGEMENT OF THE ORGANIZATION OF THE SOCIAL SPHERE - M. Pokushko; R. Pokushko; A. Pokushko (Вестник университета, 2019)
We present arguments justifying the need to build core competencies of the modern manager. Dana modern interpretation of the concepts of «competence» and «core competencies», «management core competencies». The influence of key management competencies in the management of the organization efficiency. Built competence model for managers of social service of the population. Monitoring of compliance with the actual competence of managers in the study developed competence model of social service sector managers of the Krasnoyarsk Krai. Defined development tools underdeveloped competence management organization of the social sphere.